2008
DOI: 10.1111/j.1551-2916.2007.02244.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ceramic Nanocomposite Powders with in situ Formation of Nanowires/Nanobelts

Abstract: A significant challenge in synthesizing nanowire/nanobelt‐reinforced ceramic nanocomposites is to uniformly disperse these reinforcements. Here, we report the synthesis of amorphous silicon carbonitride powders containing in situ‐formed single‐crystal Si3N4 nanowires and nanobelts via the catalyst‐assisted pyrolysis of a polymeric precursor. The nanowires/nanobelts are uniformly dispersed within the powder matrix. The ratio of nanomaterials to powder can be controlled by tailoring the experimental conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 44 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…One type is in condensed solid rods and appears dark black in color. These rods are expected to be for the Si 3 N 4 phase as dictated from the shape of Si 3 N 4 nanorods prepared with varying processes 30,36,37 . Whereas, the other type appears in a bamboo‐like structure, which is believed to be assigned for silicon carbide as mentioned by various investigators 34,36,38,39 .…”
Section: Resultsmentioning
confidence: 79%
“…One type is in condensed solid rods and appears dark black in color. These rods are expected to be for the Si 3 N 4 phase as dictated from the shape of Si 3 N 4 nanorods prepared with varying processes 30,36,37 . Whereas, the other type appears in a bamboo‐like structure, which is believed to be assigned for silicon carbide as mentioned by various investigators 34,36,38,39 .…”
Section: Resultsmentioning
confidence: 79%
“…For example, Vakifahmetogluet al [17] described the production of Si 3 N 4 and SiC nanowires using poly(methyl-phenyl)silsesquioxane (PMPS) with a cobalt catalyst. Likewise, singlecrystalline Si 3 N 4 nanowires/nanobelts were produced from polysilazane, using FeCl 2 as catalyst [18]. Yang et al reported SiCnanorods that were synthesized using a similar methodology [19].…”
Section: Introductionmentioning
confidence: 99%
“…For example, carbon nanotubes (CNTs) were synthesized from a PCS containing iron nanoparticles, 13 or from a borazine‐based precursor including nickel as catalyst, 14 while SiC/SiO 2 core/shell nanocables were produced using poly(dimethylsiloxane) coupled with ferrocene 15 . Likewise, a polysilazane was used to produce amorphous silicon carbonitride (SiCN) powder with in situ ‐grown single‐crystal Si 3 N 4 nanowires/nanobelts, using FeCl 2 as catalyst 16 . A similar methodology was also used to synthesize powders containing SiC nanorods, 17 Si 3 N 4 nanobelts, 18–20 single‐crystalline Si 3 N 4 nanowires with 21 or without 22 aluminum doping, and finally silicon‐doped boron nitride (BN) nanotubes having a bamboo structure 23 .…”
Section: Introductionmentioning
confidence: 99%